Bad boys : ride or die [videorecording (DVD)] - Bremner, Chris; Beall, Will; Smith, Will, 1968-; Lawrence, Martin, 1965-; Hudgens, Vanessa, 1988-; Ludwig, Alexander, 1992-; Núñez, Paola, 1978-; Dane, Eric, 1972-; Gruffudd, Ioan; Scipio, Jacob, 1993-; Liburd, Melanie, 1987-; Smith, Tasha, 1971-; et al. (Sony Pictures Home Entertainment, 2024)
"The world's favorite Bad Boys are back with their iconic mix of edge-of-your seat action and outrageous comedy but this time with a twist: Miami's finest are now on the run. When Captain Howard is unjustly accused of a lifetime of drug-related crimes, the Bad Boys vow to clear his name" --Container.